Alternative sequential combinations of electrocoagulation with electrooxidation and peroxi-coagulation for effective treatment of adhesive production industry wastewater - Boyraz, Berfin; Yilmaz, Ezgi Unal; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze; Demir, Ahmet (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Adhesive production industry wastewater can be characterized by high chemical oxygen demand (COD) sourced from high refractory organic contaminants and high total suspended solids (TSS) concentration. Biodegradability of the wastewater is low and wastewater quality is unstable. Various treatment processes have limited applicability in such characterized wastewater. In this study, the treatment performance of electrochemical processes was investigated. Because it is not possible to meet the discharge standards by application of only one process for high refractory organic content, sequential electrochemical processes were studied in this work. In the first step of the sequential process, electrocoagulation (EC) using Al electrodes by which better performance was achieved was applied. In the second step, electrooxidation (EO) and peroxi-coagulation (PC) processes were applied to the EC effluent. In EO, Ti/MMO was selected as the most effective anode whereas in PC, Fe was used as the anode, and graphite was used as the cathode. Box-Behnken Design was applied to optimize the operating conditions of EO and PC processes and to obtain mathematical model equations. In the EC process, 77% COD, 78.5% TSS, and 85% UV254 removal efficiency were obtained under the optimum conditions (pH 7.2, reaction time 35 min, and current density 0.5 mA/cm2). With the EO and PC processes applied to the effluent of EC, 68.5% COD, 77% TSS, and 83% UV254 removal and 77.5% COD, 87% TSS, and 86.5% UV254 removal were obtained, respectively. The specific energy consumption of EC-EO and EC-PC processes was 16.08 kWh/kg COD and 15.06 kWh/kg COD, respectively. Considering the treatment targets and process operating costs, it was concluded that both sequential electrochemical systems could be promising alternative systems for the treatment of adhesive production industry wastewater.
Keywords: Electrocoagulation; Electrooxidation; Industrial wastewater treatment; Peroxi-coagulation; Process optimization; RESPONSE-SURFACE METHODOLOGY; ADVANCED OXIDATION PROCESSES; ELECTRO-FENTON PROCESS; DOPED DIAMOND ANODE; ELECTROCHEMICAL OXIDATION; LEACHATE TREATMENT; REMOVAL; DEGRADATION; OPTIMIZATION; ALUMINUM; Environmental Sciences & Ecology